Empat Tahun E-Billing: Efektifkah? (Studi Kasus Di KPP Pratama Pamekasan) - Faisol, Moh (Unversitas Islam Madura, 2019)
The aims of this reseach to understand the effectiveness of the application of e-billing systems at Pamekasan Primary Tax Office. The research data was obtained from the documentation and interviews with one key informant and three supporting informants. The data analysis technique uses qualitative methods; reduction, presentation, verification, and conclusion as well as testing the validity of the data by using source triangulation and methods. The results of this study are the application of system e-billing, beginning with socialization by the DJP to taxpayers. The effectiveness of using e-billing is felt more comfortable and faster by taxpayers in paying taxes and can minimize data entry errors by perception bank officers. The obstacles faced by DJP in terms of the implementation of e-billing are that there are still many taxpayers who have not used e-billing because they are having difficulties when faced with technology, and consider SSP more accessible.